Implementasi Sistem Pendukung Keputusan Menggunakan Metode Promethee Dalam Pemilihan Sepeda Motor Terlaris PT. Indako Trading Co Binjai - Dinda Cahya Ramadhani; Herlina Harahap; Mufida Khairani (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
In building a best-selling motorcycle selection system, a decision support system is needed which is intended to assist decision makers in selecting the best-selling motorcycle at PT. Indako Trading Co Binjai by using data from survey results directly to the location. This system will be designed using the web and perform calculations using the Promethee Method. Where there are already determined criteria and alternatives which will later bring up an output of the best-selling motorcycle type at PT. Indako Trading Co Binjai. Based on the results of the analysis and design that has been carried out in the Promethee stage in calculating the Net Flow value, the first ranking results in the selection of the best-selling motorcycle at PT. Indako Trading Co Binjai is Vario 150.